An interpersonal approach to modelling business-to-business relationship quality - Vieira, Armando Luis (2008)
In the last two decades, we have been watching a dramatic change in the nature of buyer-seller relationships. Relationship quality (RQ) is nowadays seen as the source of superior performance and competitive advantage, rather than service quality and/or customer satisfaction. As firms move towards closer, more collaborative relationships, the role of relationship managers as marketers is increasingly vital to organisational success. Despite the crucial role that relationship managers play in building business-to-business (B2B) RQ, very little research has looked at the key constructs of inter-organisational RQ from an interpersonal approach.